Cardiometabolic parameters and novel hematological indices in women with migraine: Novel hematological indices in migraine - Klisic, Aleksandra; Tmusic, Ana (Journal of Medical Biochemistry, 2026)
Objective: The pathophysiological aspect of migraine has not been fully elucidated. It is assumed that inflammation is at the root of this disease. The goal of the research is to examine cardiometabolic and novel hematological indices in patients with migraine.Methods: A total of 50 women diagnosed with migraine were included in the study. Women were recruited during pain-free periods between pain attacks. The control group consisted of 25 age-matched healthy women. The MIDAS score (Migraine Disability Assessment score) was calculated. Results: Women with migraine had higher levels of uric acid (P=0.045) and higher activity of transaminases, AST (P
Keywords: coagulation; inflammation; migraine; plateletes